Metacognitive Therapy in Patients with Obsessive-Compulsive Disorder: A review - Atmaca, Murad (Aves, 2022)
Metacognitive therapy is a relatively novel and growing psychotherapeutic approach. Within the last 20 years, several metacognitive-oriented therapy methods have been developed. They are metacognitive therapy which was developed by Wells, metacognitive training which was produced by Moritz et al. especially for patients with psychotic disorder, and metacognitive reflection and insight therapy for psychotic patients. Among them, the most structured one seems the metacognitive therapy. The main notion of metacognitive therapy is to alter the dysfunctional metacognitive interpretations and strategies underlying psychopathology. However, it should be emphasized that it has some fundamental differences from cognitive behavioral therapy because metacognitive therapy is a relatively new school of cognitive therapy, its effectiveness in the treatment of many psychiatric disorders continues to be evaluated intensively. Obsessive-compulsive disorder is one of these disorders. As obsessive-compulsive disorder is a lifelong disorder that causes significant loss of workforce and pharmacotherapy is sometimes insufficient, psychotherapeutic approaches are of great importance. In this context, exposure and response prevention still seems to be an important treatment option in terms of psychotherapeutic approaches. However, it is clear that a new approach is required in psychiatry practice in cases where exposure and response prevention and classical cognitive behavioral therapy are not sufficient and remain with residual symptoms. In this respect, metacognitive therapy can be an important alternative to fill this gap. However, more evidence needs to be created with studies with much larger samples.
Keywords: MCI; metacognitive therapy; obsessive-compulsive disorder